BEBERAPA FAKTOR YANG MEMPENGARUHI KEPATUHAN KONSUMSI TABLET FE - Handayani, Sekar; Aisyah, Aisyah; Wirawan, Susilo; Amanupunnyo, Notesya Astri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Anemia in adolescents can occur due to malnutrition. Adolescent girls experience a lot of nutrient deficiencies in their daily consumption. consumption on a daily basis. Based on document searches, Lampung province is one of the provinces with the highest province with the proportion of adherence to consumption of blood supplement tablets in adolescents below the national average. Below the national average. The aim of the study was to determine several factors affecting Fe tablet consumption compliance. Research design The research design used in this study was cross sectional. The study was conducted in 10 junior high schools in the working area of the Natar Health Center in July 2024. Population population was all adolescent girls totaling 315 respondents with a sample of 108 respondents. 108 respondents. The sampling technique used Stratified Random sampling. The research instrument used research questionnaire. Data analysis was carried out univariate and bivariate. Results The results showed that there was a relationship between motivation (p value: 0.040) and peer support (p value: 0.019) on compliance with Fe tablet consumption in adolescent girls. It is recommended for adolescent girls to proactively seek information on the benefits of Fe tablets as an effort to prevent anemia early on. tablets as an effort to prevent anemia early on.Keywords: Motivation, Adolescent Girls, Fe Tablets.